Promoting Your School: A Public Relations Handbook - Lober, Irene (Rowman & Littlefield Publishers, 1997)
Schools today are experiencing pressures that have never been faced before. Very often members of the public do not know how their schools are doing, and as a result voters respond negatively. In Promoting Your School: A Public Relations Handbook, Irene Lober clearly describes various processes, methods, and actions that schools can take to better disseminate their message to their district. By focusing on public relations and sharing information about school performance, districts can have a better sense of what is working and as a result support their schools better.